Kajian Efisiensi Penyisihan BOD pada Start-Up Bioreaktor Hibrid Anaerob Menggunakan Substrat Limbah Cair Pabrik Sagu - Handayani, K.H Sri; Ahmad, Adrianto; Bahruddin (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2025)
The Meranti Islands Regency is renowned as one of the largest sago flour producers in Indonesia, with a total production of 202,186 tons of sago per year and wastewater production reaching 40,000 liters. The microorganism Enterobacter aerogenes is a facultative anaerobic hydrogen-producing bacterium through dark fermentation of sago liquid waste. This study aims to determine study on bod removal efficiency during the start-up phase of a hybrid anaerobic bioreactor, identify the biological oxygen demand (BOD) loading rate during start-up, and evaluate the BOD removal efficiency in the start-up phase. The sago wastewater was characterized for its BOD, pH, and VSS content before treatment. The first phase involved preparing cow dung extract, which serves as a medium. The second phase focused on biomass seeding and acclimatization using a sago medium. The acclimatization process utilized a daily discharge-and-fill method of 200 mL (total acclimatization volume of 12.5 L). Samples from the acclimatization process were analyzed for potential of hydrogen (pH) and volatile suspended solid (VSS) values. If the acclimatized VSS values were below 10%, the third phase (start-up phase) was initiated. The start-up phase was operated with a hydraulic retention time (HRT) of 48 hours. Output samples were analyzed for pH, VSS, and %BOD values until a consistent %BOD value below 10% was achieved. The final stage involved data collection for analyzing the kinetics of microorganism cell growth. The specific growth kinetics value (µ) of the mixed-culture microorganism cells during the start-up phase calculated with a result of μ=0.00617. The highest BOD loading rate during the start-up phase occurred at the 1st hydraulic retention time (HRT), reaching 6.54 kg/m³/day, accompanied by the lowest BOD removal efficiency of 18.76%. In contrast, the lowest BOD loading rate was recorded at the 11th HRT, at 0.704 kg/m³/day, achieving the highest BOD removal efficiency of 91.26%.